The Influence of Price and Product Quality on Consumer Decisions to Purchase Oppo Smartphones in Bengkulu City - M. Ronaldo Aprilio; Ermy Wijaya; Iswidana Utama Putra (Journal of Law, Social Science, and Management Review, 2026)
This objective of this research is to know influence of price and product quality toward customer decision to buy Oppo Smartphone in the Bengkulu City. Type of this research is descriptive quantitative approaches. The type of the data being used is the primary data obtained through the dissemination of questionnaires and observation. Respondent in the research are customer which bought of Oppo Smartphone in the Bengkulu City taking by proportional random sampling.  The respondent was used 115 respondents. Data analysis method were use multiple regression linear. Based on data analysis find out results that’s: (1) the price has a significant influence toward customer decision to buy Oppo Smartphone in the Bengkulu City; (2) the product quality has a significant influence toward customer decision to buy Oppo Smartphone in the Bengkulu City; and (3) the price and product quality by together has a significant influence toward customer decision to buy Oppo Smartphone in the Bengkulu City.